Effect of Apium Graveolens (Celery) Seed Extract on Serum Uric Acid Level of Hyperuricemic Rats and its Comparison with Allopurinol - Abdul Karim; Shabbir Ali bhatti; Noman Johnson; Mahreen Akhtar; Sundus Mona; Zartasha Safdar (Journal of Shalamar Medical & Dental College, 2021)
Background: Plant derived medicines are widely used in traditional culture all over the world.